Repurposing Antidiabetic Drugs for Cardiovascular Disease - Schubert, Mario; Hansen, Sinah; Leefmann, Julian; Guan, Kaomei (Frontiers in Physiology, 2020)
Metabolic diseases and diabetes represent an increasing global challenge for human health care. As associated with a strongly elevated risk of developing atherosclerosis, kidney failure and death from myocardial infarction or stroke, the treatment of diabetes requires a more effective approach than lowering blood glucose levels. This review summarizes the evidence for the cardioprotective benefits induced by antidiabetic agents, including sodium-glucose cotransporter 2 inhibitor (SGLT2i) and glucagon-like peptide-1 receptor agonist (GLP1-RA), along with sometimes conversely discussed effects of dipeptidyl peptidase-4 inhibitor (DPP4i) and metformin in patients with high cardiovascular risk with or without type 2 diabetes. Moreover, the proposed mechanisms of the different drugs are described based on the results of preclinical studies. Recent cardiovascular outcome trials unexpectedly confirmed a beneficial effect of GLP-1RA and SGLT2i in type 2 diabetes patients with high cardiovascular risk and with standard care, which was independent of glycaemic control. These results triggered a plethora of studies to clarify the underlying mechanisms and the relevance of these effects. Taken together, the available data strongly highlight the potential of repurposing the original antidiabetics GLP1-RA and SGLT2i to improve cardiovascular outcome even in non-diabetic patients with cardiovascular diseases.